Evolution of chain migration in an aerial insectivorous bird, the common swift Apus apus. (1st October 2020) - Åkesson, Susanne; Atkinson, Phil W.; Bermejo, Ana; de la Puente, Javier; Ferri, Mauro; Hewson, Chris M.; Holmgren, Jan; Kaiser, Erich; Kearsley, Lyndon; Klaassen, Raymond H. G.; Kolunen, Heikki; Matsson, Gittan; et al.
Abstract: Spectacular long‐distance migration has evolved repeatedly in animals enabling exploration of resources separated in time and space. In birds, these patterns are largely driven by seasonality, cost of migration, and asymmetries in competition leading most often to leapfrog migration, where northern breeding populations winter furthest to the south. Here, we show that the highly aerial common swift Apus apus, spending the nonbreeding period on the wing, instead exhibits a rarely found chain migration pattern, where the most southern breeding populations in Europe migrate to wintering areas furthest to the south in Africa, whereas the northern populations winter to the north. The swifts concentrated in three major areas in sub‐Saharan Africa during the nonbreeding period, with substantial overlap of nearby breeding populations. We found that the southern breeding swifts were larger, raised more young, and arrived to the wintering areas with higher seasonal variation in greenness (Normalized Difference Vegetation Index) earlier than the northern breeding swifts. This unusual chain migration pattern in common swifts is largely driven by differential annual timing and we suggest it evolves by prior occupancy and dominance by size in the breeding quarters and by prior occupancy combined with diffuse competition in the winter.